From Waste to Fashion – A Fashion Upcycling Contest: A Critical Review - Kasma Manggala; Bhenu Artha; Utami Tunjung Sari; Niken Permata Sari; Antonius Satria Hadi; Bahri Bahri; Cahya Purnama Asri (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
The paper presents a case study of the TAP (Portuguese Airline Company) Upcycling Project, which challenged two young fashion designers to create garments from waste textiles sourced from decommissioned aircraft. The work is positioned within the broader context of circular economy and sustainability in the fashion industry, demonstrating how creative design processes can transform industrial waste into valuable fashion products. This critical review also emphasizes emerging research directions and strategies where advanced characterization and design approaches may help unlock the full potential of fashion upcycling.